Effects of the herbicide dicamba on nontarget plants and pollinator visitation. (24th November 2015) - Bohnenblust, Eric W.; Vaudo, Anthony D.; Egan, J. Franklin; Mortensen, David A.; Tooker, John F.
Abstract: Nearly 80% of all pesticides applied to row crops are herbicides, and these applications pose potentially significant ecotoxicological risks to nontarget plants and associated pollinators. In response to the widespread occurrence of weed species resistant to glyphosate, biotechnology companies have developed crops resistant to the synthetic‐auxin herbicides dicamba and 2, 4‐dichlorophenoxyacetic acid (2, 4‐D); and once commercialized, adoption of these crops is likely to change herbicide‐use patterns. Despite current limited use, dicamba and 2, 4‐D are often responsible for injury to nontarget plants; but effects of these herbicides on insect communities are poorly understood. To understand the influence of dicamba on pollinators, the authors applied several sublethal, drift‐level rates of dicamba to alfalfa ( Medicago sativa L.) and Eupatorium perfoliatum L. and evaluated plant flowering and floral visitation by pollinators. The authors found that dicamba doses simulating particle drift (≈1% of the field application rate) delayed onset of flowering and reduced the number of flowers of each plant species; however, plants that did flower produced similar‐quality pollen in terms of protein concentrations. Further, plants affected by particle drift rates were visited less often by pollinators. Because plants exposed to sublethal levels of dicamba may produce fewer floral resources and be less frequently visited by pollinators, use of dicamba or other synthetic‐auxin herbicides with widespread planting of herbicide‐resistant crops will need to be carefully stewarded to prevent potential disturbances of plant and beneficial insect communities in agricultural landscapes. Environ Toxicol Chem 2016;35:144–151. © 2015 SETAC